Compact Aberration‐Corrected Spectrometers in the Visible Using Dispersion‐Tailored Metasurfaces. Issue 14 (9th December 2018) - Zhu, Alexander Y.; Chen, Wei Ting; Sisler, Jared; Yousef, Kerolos M. A.; Lee, Eric; Huang, Yao‐Wei; Qiu, Cheng‐Wei; Capasso, Federico
Abstract: The spectral resolution and range of conventional spectrometers are typically limited by optical aberrations of their focusing elements, mainly due to chromatically induced astigmatism and an intrinsically curved focal plane. Traditional approaches to overcome this challenge require additional optical components which introduce significant bulk and design complexity to the system and prevent easy integration with portable devices. Here a single planar off‐axis focusing metalens consisting of subwavelength TiO2 nanofins whose focal spots lie along a plane and undergo minimal focal spot broadening for almost 200 nm across the visible spectrum is demonstrated. This allows us to achieve a miniature aberration‐corrected spectrometer with nanometer spectral resolution, while having a beam propagation distance of only 4 cm to the camera plane. This is achieved by dispersion engineering: tailoring the phase, group delay (GD) and GD dispersion of the metalens. This approach is general and can also be used to introduce customized functionalities to the metalens such as a linear dispersion in the frequency domain with minimal additional overhead. Abstract : Optical spectroscopy is an essential tool used in many areas such as food monitoring and medical diagnostics. However, spectrometers typically face a trade‐off between their spectral resolution, working wavelength range, and overall device size due to optical aberrations. Here a highly compact, aberration‐corrected spectrometer with nanometer resolution across most of the visible spectrum using off‐axis metalenses is presented.